Self-supporting integrated oxygen vacancy heterogeneous site independent electrode and preparation method and application thereof

Self-supported integrated cobalt aluminum oxide independent electrodes are prepared through vacuum arc smelting and dynamic atomic dissolution self-assembly technology, and oxygen vacant heterogeneous sites are constructed through electrochemical electrostatic coordination reaction, which solves the complexity of the preparation process and poor conductivity of traditional electrode materials. The problem of the supercapacitor improves the electrochemical performance and service life.

CN119170427APending Publication Date: 2024-12-20TAIZHOU UNIV (ZHEJIANG)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411365659.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The preparation process of traditional supercapacitor electrode materials is complex and requires binder and conductive agent, which leads to blockage of reactive sites, poor structural stability, short service life, and poor conductivity, and severe capacitance attenuation during charge and discharge cycles.

Method used

Cobalt-aluminum oxide precursor alloy was prepared by vacuum arc smelting, and self-supported integrated cobalt-aluminum oxide independent electrode was prepared through dynamic atomic dissolution self-assembly technology, and CoMn2O4/Mn3O4/MnAl2O4(OV) nanometers were constructed in combination with electrochemical electrostatic coordination reaction. The heterogeneous sites of the spinel oxygen vacancy avoid the use of current collectors and binders.

Benefits of technology

It realizes controllability of structural morphology, improves the structural stability and service life of the material, reduces capacitance attenuation, enhances electrochemical performance, simplifies the preparation process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170427A_ABST
    Figure CN119170427A_ABST
Patent Text Reader

Abstract

The invention discloses a self-supporting integrated oxygen vacancy heterogeneous site independent electrode and a preparation method and application thereof. According to the invention, the self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (OV) nanosheet spinel oxygen vacancy heterogeneous site independent electrode is dynamically constructed by adopting an in-situ double-reaction strategy. The electrode has the advantages of high response rate, high structural stability, high area specific capacitance and long service life, and does not need an adhesive, a conductive agent, a current collector and the like as a self-supporting integrated independent electrode of the supercapacitor. The self-supporting integrated independent electrode prepared by the method disclosed by the invention has the advantages of high controllability of a preparation process, good structural stability of an obtained product, long service life, excellent energy storage characteristic, suitability for industrial production and the like, can be widely applied to the fields of energy storage, catalysis, seawater desalination and the like, and has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Oxygen vacancy heterogeneous site independent electrode, belonging to the technical field of transition metal oxide energy material preparation. Background Art

[0002] Energy crisis is one of the hottest topics in the world today. As an emerging energy storage system, supercapacitors have the advantages of portability, economy and high inherent safety, and play an important role in many fields. In renewable energy power generation, supercapacitors can balance the load of the power grid, improve power supply reliability and power system stability; in electric vehicles, combined with hybrid power systems of high energy density components such as batteries, they can effectively increase the service life of batteries and improve the driving range. It is a promising renewable energy storage device.

[0003] Cobalt-manganese-based transition metal oxides, as a pseudocapacitive material with high theoretical specific capacitance and low price, have become a hot research material due to their narrow band gap, unfilled d orbitals, variable crystal structure, rich valence states, multi-electron reactions, and easily regulated surface charge states. Electrode materials prepared by traditional methods need to be grown on current collectors such as nickel foam or other carbon substrates. The preparation process is relatively complicated and relies on binders and conductive agents to prepare electrodes. This preparation method has many shortcomings: first, the additives cover the surface of the active material, blocking a part of the effective reaction sites of the electrode; second, the side reaction products produced by the irreversible reaction of the binder and the conductive agent lead to an increase in interface resistance and a decrease in capacity; in addition, the interface of the traditional heterogeneous sites grown on the current collector is relatively loose and the structural stability is poor, which can easily cause structural collapse during the ion extraction process, resulting in a serious attenuation of the service life. Therefore, enhancing the activity of the active sites and the structural stability of the material is crucial for the development of new energy materials. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a self-supporting integrated independent electrode, so as to solve the problem that the preparation of the electrode requires a binder, a conductive agent and a complex current collector process.

[0005] The second purpose of the present invention is to provide a method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode to solve the problem of poor conductivity of transition metal oxides and severe capacitance attenuation during charge and discharge cycles.

[0006] A third object of the present invention is to provide a self-supporting integrated oxygen vacancy heterogeneous site independent electrode for use as a supercapacitor anode.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention is to provide a method for preparing a self-supporting integrated cobalt aluminum oxide independent electrode with controllable structure and morphology. First, a precursor alloy is prepared by a vacuum arc melting furnace, and then a self-supporting integrated cobalt aluminum oxide independent electrode is prepared by dynamic atomic dissolution self-assembly technology.

[0009] The specific preparation steps of the precursor alloy are as follows:

[0010] Step 1: Weigh aluminum and cobalt metal particles according to an atomic ratio of 65:35, and melt them into alloy ingots in a vacuum arc melting furnace;

[0011] Step 2: Cut the smelted alloy ingot into alloy sheets, degrease and clean them, then vacuum dry them for later use.

[0012] Preferably, the pressure in the vacuum melting furnace in step 1 is 5×10 -3 MPa, the atmosphere during smelting was argon protective gas, and the alloy ingot was smelted 4 times.

[0013] Preferably, the alloy sheets cut from the alloy ingot in step 2 have a size of 10×10×1 mm.

[0014] Preferably, the step of degreasing and cleaning the alloy sheet in step 2 is: ultrasonic cleaning in acetone, ethanol and deionized water for 5-15 minutes respectively.

[0015] Preferably, the vacuum drying in step 2 is carried out at a temperature of 50-70° C. and for a time of 12-24 hours.

[0016] The specific steps of the self-supporting integrated cobalt aluminum oxide independent electrode are as follows:

[0017] Step 3: First, the alloy sheet cleaned and dried in step 2 is placed in a 1-3 mol / L NaOH alkaline solution and kept in a 50°C constant temperature water bath for 1-36 hours, and then placed in a 2 mol / L HCl acidic solution and kept in a 50°C constant temperature water bath for 12 hours to achieve a dynamic atomic dissolution self-assembly process;

[0018] Step 4: After cleaning and drying the alloy sheet obtained in step 3, place it in a tubular furnace and perform annealing treatment in an argon atmosphere to obtain a self-supporting integrated cobalt aluminum oxide independent electrode.

[0019] Preferably, the heating rate of the annealing treatment condition in the tubular furnace in step 4 is 5°C / min to 500-550°C, and the temperature is kept at this temperature for 120-240min.

[0020] The present invention achieves targeted regulation of structural morphology by regulating the concentration of NaOH alkaline solution and reaction time in the dynamic atomic dissolution self-assembly reaction. A series of self-supporting integrated cobalt aluminum oxide independent electrode structures such as micro-nano clusters, corals, micro-nano flowers and nanosheets are designed.

[0021] The second aspect of the present invention is to solve the problem of poor conductivity of transition metal oxides and severe capacitance attenuation during charge and discharge cycles, and to construct dense oxygen vacancy heterogeneous sites on a self-supporting integrated cobalt aluminum oxide independent electrode in combination with electrochemical electrostatic coordination reaction.

[0022] Step 5: In an electrochemical workstation, the self-supporting integrated cobalt aluminum oxide independent electrode is subjected to an electrochemical electrostatic coordination reaction. The electrochemical electrostatic coordination reaction voltage is set to -1.0V to -1.5V, and the electrochemical electrostatic coordination reaction time is 10-30min. After the electrostatic coordination reaction, the electrode is taken out for cleaning and drying to construct a self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4(O V ) Nanosheet spinel oxygen vacancy heterosite as a standalone electrode for supercapacitors.

[0023] Preferably, the three-electrode system of the electrochemical electrostatic coordination reaction in step 5 is composed of: a cobalt aluminum oxide independent electrode as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode. The electrochemical electrostatic coordination reaction solution is composed of: adding a manganese salt and urea in a molar ratio of 1:1 to water, stirring to form a 0.15 mol / L reaction solution, wherein the manganese salt is manganese chloride or manganese nitrate.

[0024] The CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Nanosheet spinel oxygen vacancy heterogeneous site materials, as self-supporting integrated independent electrodes, do not require additional current collectors as supporting materials, have strong structural stability, alleviate the structural collapse during the ion insertion and extraction process, and thus increase the service life of the material. In addition, the addition of adhesives and conductive agents is avoided, reducing the capacitance decay caused by irreversible reactions.

[0025] The third aspect of the present invention provides the self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V )Application of nanosheet spinel oxygen vacancy heterosite independent electrodes.

[0026] The self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V) Nanosheet spinel oxygen vacancy heterogeneous site independent electrode can be directly used as supercapacitor anode. Cyclic voltammetry (CV), constant current charge and discharge (GCD) and cycle stability tests were performed in an electrochemical workstation with 1 mol / L KOH as the electrolyte. According to the GCD curve, the area specific capacitance of the self-supporting integrated independent electrode, the energy density and power density of the device can be calculated according to formulas 1-1 to 1-3:

[0027]

[0028]

[0029]

[0030] Where I is the current (A), Δt is the discharge time (s), and S is the effective area of ​​the electrode material (cm 2 ), ΔV is the discharge potential window value (V), C S is the area specific capacitance of the supercapacitor electrode (2mA / cm 2 , 17700.32mF / cm 2 ) and good cycle stability (6mA / cm 2 , after 5000 cycles, the capacitance retention rate is 92.32%). According to Formula 1-2 and Formula 1-3, the energy density and power density of the device can be calculated (E = 81.56Wh / cm 2 , P = 81.56W h / cm 2 ; E = 45.40Wh / cm 2 , P = 3968.68W h / cm 2 ).

[0031] By adopting the above scheme, the synthesis of multi-metal element precursors can be achieved in one step through vacuum arc melting technology, breaking through the shackles of multi-element complex processes. Using the optimized dynamic atomic dissolution self-assembly process, the synthesized micro-nanosheet structure is used as a self-supporting integrated independent electrode, which does not require a current collector and a binder, simplifies the preparation process and reduces production costs. At the same time, it alleviates the problem of capacitance attenuation caused by side reactions of binders, conductive agents, etc., and provides a feasible solution for the synthesis of self-supporting integrated independent electrodes. Further combined with the electrochemical electrostatic coordination reaction, oxygen vacancy heterogeneous sites are designed on the self-supporting integrated cobalt aluminum oxide independent electrode, which alleviates the structural instability problem caused by the loose interface of the heterogeneous sites synthesized by the traditional method, and provides an efficient and feasible strategy for the preparation of dense oxygen vacancy heterogeneous sites.

[0032] The built-in electric field effect induced by the oxygen vacancy heterogeneous site constructed by the present invention and the large-scale electron-hole can effectively promote the ion diffusion dynamics and facilitate efficient and rapid charge transfer. In addition, the introduction of oxygen vacancy defects can change the band structure and surface charge characteristics of the semiconductor. The good synergistic effect between the heterogeneous site and the oxygen vacancy defect can optimize the adsorption performance, promote the charge transfer process and structural stability, and achieve a significant improvement in electrochemical performance.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The self-supporting integrated cobalt aluminum oxide independent electrode prepared by the vacuum arc melting and dynamic atomic dissolution self-assembly technology adopted in the present invention has good structural stability. On the one hand, no binder and conductive agent are required, which simplifies the process complexity of preparing the electrode; on the other hand, the occurrence of side reactions is reduced, and the side reaction products are prevented from covering and clogging the effective surface area of ​​the electrode, thereby improving the charge storage of the material.

[0035] 2. The present invention can achieve controllable construction of structural morphology and oxygen vacancy heterogeneous sites by adjusting parameters such as dynamic atomic dissolution self-assembly process parameters, heat treatment process, electrolyte type of electrochemical electrostatic coordination reaction, reaction potential and reaction time.

[0036] 3. The nanosheet / spinel structure prepared by the present invention provides abundant reactive sites for redox reactions during the charge and discharge process. At the same time, it has a good stress relief mechanism, effectively improves the cycle life of the material, and alleviates the severe attenuation of specific capacitance.

[0037] 4. Compared with precious metal raw materials, the cobalt-manganese-based oxide used in the present invention has low preparation cost and strong controllability of structural morphology. It can be used as a multifunctional application material such as energy storage, catalysis and seawater desalination, and is more adaptable to practical application needs.

[0038] 5. The self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Nanosheet spinel oxygen vacancy heterosite-independent electrodes can be used as anodes in supercapacitors.

[0039] 6. The present invention uses rGO as the negative electrode to assemble an aqueous supercapacitor, which has excellent electrochemical performance and an energy density of 81.56Wh / cm 2 When the power density reaches 639.93W / cm 3 .

[0040] 7. The present invention solves the problems of slow diffusion kinetics and poor structural stability of electrode materials by constructing oxygen vacancy heterogeneous sites, greatly improves the energy density and service life of the device, and achieves the purpose of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the self-supporting integrated independent electrode prepared in Example 1 of the present invention.

[0042] Figure 2 This is a SEM image of the self-supporting integrated independent electrode prepared in Example 2 of the present invention.

[0043] Figure 3 This is a SEM image of the self-supporting integrated independent electrode prepared in Example 3 of the present invention.

[0044] Figure 4 This is a SEM image of the self-supporting integrated independent electrode prepared in Example 4 of the present invention.

[0045] Figure 5 These are XRD images of the precursor alloy sheets prepared in Examples 1-4 of the present invention and the self-supporting integrated cobalt aluminum oxide independent electrode of Example 4.

[0046] Figure 6 The self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) SEM image of the nanosheet spinel oxygen vacancy heterosite independent electrode.

[0047] Figure 7 CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) HRTEM and SAED patterns of independent electrodes.

[0048] Figure 8 The self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) XRD pattern of the nanosheet spinel oxygen vacancy heterosite independent electrode.

[0049] Fig. 9 CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) GCD curve of the independent electrode and the GCD curve of the aqueous supercapacitor device assembled with rGO as the negative electrode.

[0050] Fig.10 The water-based supercapacitor device of Example 4 of the present invention is 8 mA / cm 2 Figure 3. Cyclic stability test diagram after 5000 cycles at high current density (the inset is the GCD curve of the last 5 cycles). DETAILED DESCRIPTION

[0051] The present invention provides a method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode with controllable structure and morphology. First, a precursor alloy is prepared by vacuum arc melting, and then a self-supporting integrated cobalt aluminum oxide independent electrode is prepared by combining dynamic atomic dissolution self-assembly technology; further, an electrochemical electrostatic coordination reaction is combined to prepare a self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Nanosheet spinel oxygen vacancy heterogeneous site independent electrode.

[0052] The preparation of the precursor alloy by vacuum arc melting includes the following steps:

[0053] Step 1: Weigh aluminum and cobalt metal particles according to an aluminum to cobalt atomic ratio of 65:35, and melt them into alloy ingots in a vacuum arc melting furnace;

[0054] Step 2: Cut the smelted alloy ingot into alloy sheets, degrease and clean them, then vacuum dry them for later use.

[0055] The method for preparing a self-supporting integrated cobalt aluminum oxide independent electrode by combining dynamic atomic dissolution self-assembly technology comprises the following steps:

[0056] Step 3: placing the alloy sheet cleaned and dried in step 2 in NaOH alkaline solution and HCl acidic solution in sequence, and controlling the concentration and time to realize the self-assembly process of dynamic atomic dissolution;

[0057] Step 4: After cleaning and drying the alloy sheet obtained in step 3, place it in a tubular furnace and perform annealing treatment under an argon protective atmosphere to obtain a self-supporting integrated cobalt aluminum oxide independent electrode.

[0058] The invention combines electrostatic coordination reaction to prepare a self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Nanosheet spinel oxygen vacancy heterogeneous site independent electrode, the preparation method comprises the following steps:

[0059] Step 5: In an electrochemical workstation, the self-supporting integrated cobalt aluminum oxide independent electrode is subjected to an electrochemical electrostatic coordination reaction. The electrochemical electrostatic coordination reaction voltage is set to -1.0V to -1.5V, and the electrochemical electrostatic coordination reaction time is 10-30min. After the electrostatic coordination reaction, the electrode is taken out for cleaning and drying. V ) Oxygen vacancy heterosite freestanding electrodes for supercapacitors.

[0060] The electrode material can achieve controllable design of structural morphology and oxygen vacancy heterogeneous sites by adjusting process parameters such as dynamic atomic dissolution self-assembly process parameters, heat treatment process parameters, solution type of electrochemical electrostatic coordination reaction, reaction potential and reaction time. And the oxygen vacancy heterogeneous sites constructed using the present invention have the advantage of being dense and compact, overcoming the problem of poor structural stability caused by loose heterogeneous interfaces. And using the dynamic atomic dissolution self-assembly technology in the present invention, targeted regulation of material structure morphology can be achieved, and the construction of multi-oxide heterogeneous sites can be achieved in one step, broadening the types of multi-oxide synthesis of materials.

[0061] The technical solution of the present invention is further described by the following embodiments, but these embodiments should not be construed as limiting the technical solution of the present invention.

[0062] Embodiment 1:

[0063] This embodiment provides a self-supporting integrated independent electrode, which is prepared by the following steps:

[0064] Aluminum and cobalt metal particles were weighed according to the atomic ratio of 65:35, and the total mass of aluminum and cobalt was about 30g. A vacuum arc melting furnace was used to melt the alloy ingots. The vacuum environment of the vacuum arc melting was 5×10 -3 MPa, the atmosphere during smelting was argon protective gas, and the alloy ingot was smelted 4 times. The smelted alloy ingot was cut into alloy sheets with a size of 10×10×1mm, and ultrasonically degreased and cleaned in acetone, ethanol and deionized water for 5-15min, respectively, and then vacuum dried at 60℃ for 12h to obtain the precursor alloy sheet.

[0065] The alloy sheet obtained above was placed in a constant temperature water bath of 50°C containing 1 mol / L NaOH alkaline solution for 12 hours, and then placed in a constant temperature water bath of 50°C containing 2 mol / L HCl acidic solution for 12 hours, and then cleaned and dried. The dried alloy sheet was then placed in a tubular furnace preheated to 550°C, and kept warm for 120 minutes under an argon protective atmosphere, with a heating rate of 5°C / min.

[0066] Figure 1 This is a SEM image of the dynamic dissolution self-assembly technology used in Example 1. It can be seen that the morphology is mainly composed of an intricate nanowire network.

[0067] Figure 5The black XRD spectrum is the XRD pattern of the precursor alloy sheet prepared in Example 1 of the present invention. It can be seen that the diffraction angles 2θ of 13.26°, 23.27°, 44.83°, 47.31° and 47.57° correspond to the (100), (110), (203), (220) and (302) crystal planes of Al5Co2, respectively. At the same time, the diffraction angles 2θ of 31.29°, 44.83° and 74.14° correspond to the (100), (110), (203), (220) and (302) crystal planes of Al5Co2, respectively. 0.52 Co 0.48 In summary, the phase composition of the precursor is Al5Co2 / Al 0.52 Co 0.48 .

[0068] Embodiment 2:

[0069] The same method as in Example 1 was adopted to prepare the precursor alloy sheet. The alloy sheet obtained above was placed in a constant temperature water bath of 50°C containing a 2mol / L NaOH alkaline solution for 12 hours, and then placed in a constant temperature water bath of 50°C containing a 2mol / L HCl acidic solution for 12 hours, and then cleaned and dried. The dried alloy sheet was then placed in a tubular furnace preheated to 550°C, and kept warm for 120 minutes under an argon protective atmosphere, with a heating rate of 5°C / min.

[0070] Figure 2 This is a SEM image of Example 2 controlled by dynamic dissolution self-assembly technology. The morphology is mainly composed of nanosheets with uniform thickness and micro-nanospheres of different sizes. The thickness of the nanosheets is about 20nm, and the diameter of the micro-nanospheres varies from about 8 to 10μm.

[0071] Same as Example 1, Figure 5 The black XRD spectrum is the XRD spectrum of the precursor alloy sheet prepared in Example 1 of the present invention.

[0072] Embodiment 3:

[0073] The same method as in Example 1 was adopted to prepare the precursor alloy sheet. The alloy sheet obtained above was placed in a constant temperature water bath of 50°C containing a 3 mol / L NaOH alkaline solution for 24 hours, and then placed in a constant temperature water bath of 50°C containing a 2 mol / L HCl acidic solution for 12 hours, and then cleaned and dried. The dried alloy sheet was then placed in a tubular furnace preheated to 550°C, and kept warm for 120 minutes under an argon protective atmosphere, with a heating rate of 5°C / min.

[0074] Figure 3This is a SEM image of the dynamic dissolution self-assembly technology used in Example 3. The morphology is mainly a micro-nano porous morphology composed of different pore sizes, and the pore size ranges from 100 to 360 nm.

[0075] Same as Example 1, Figure 5 The black XRD spectrum is the XRD spectrum of the precursor alloy sheet prepared in Example 1 of the present invention.

[0076] Embodiment 4:

[0077] The same method as in Example 1 was adopted to prepare the precursor alloy sheet. The alloy sheet obtained above was placed in a constant temperature water bath of 50°C containing a 2mol / L NaOH alkaline solution for 24 hours, and then placed in a constant temperature water bath of 50°C containing a 2mol / L HCl acidic solution for 12 hours, and then cleaned and dried. The dried alloy sheet was then placed in a tubular furnace preheated to 550°C, and kept warm for 120 minutes under an argon protective atmosphere, with a heating rate of 5°C / min.

[0078] Figure 4 This is a SEM image of the dynamic dissolution self-assembly technology used in Example 4. The morphology is mainly composed of intricately crossed nanosheets, and the thickness of the nanosheets is about 50-80nm.

[0079] Same as Example 1, Figure 5 The black XRD spectrum is the XRD pattern of the precursor alloy sheet prepared in Example 1 of the present invention. The red XRD spectrum is the phase characterization after dynamic atomic dissolution self-assembly. At positions where 2θ is 36.50°, 42.40° and 61.52°, it corresponds to the (111), (200) and (220) crystal planes of CoO. In addition, the diffraction peaks at diffraction angles 2θ of 18.99°, 31.25°, 36.82° and 65.22° correspond to the (111), (220), (311) and (440) crystal planes of CoAl2O4. In summary, the phase composition after dynamic atomic self-assembly is CoO and CoAl2O4.

[0080] Example 4 is a preferred embodiment of the present invention, and oxygen vacancy heterogeneous sites are constructed by electrochemical electrostatic coordination reaction. The alloy sheet after annealing in Example 4 is subjected to electrochemical electrostatic coordination reaction in an electrochemical workstation to prepare cobalt-manganese-based metal oxide oxygen vacancy heterogeneous sites. In order to further explore the effect of electrochemical electrostatic coordination reaction on heterogeneous structure, two different manganese salt electrochemical electrostatic coordination reaction solutions are selected to construct oxygen vacancy heterogeneous structure. The deposition voltage is set to -1.5V, and the deposition time is 30min. After deposition, it is taken out for cleaning and drying to prepare CoMn2O4 / Mn3O4 / MnAl2O4 (O V) Nanosheet spinel oxygen vacancy heterosite self-supporting integrated independent electrode for supercapacitors.

[0081] The three-electrode system of the electrochemical electrostatic coordination reaction is composed of: a cobalt aluminum oxide independent electrode as the working electrode, a platinum electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrochemical electrostatic coordination reaction solution is composed of: the first coordination reaction solution is to add manganese chloride and urea in a molar ratio of 1:1 to 100 mL of water, and then stir the solution evenly by electromagnetic stirring for 30 minutes to form a 0.15 mol / L manganese chloride solution; the second coordination reaction solution is to add manganese nitrate and urea in a molar ratio of 1:1 to 100 mL of water, and then stir the solution evenly by electromagnetic stirring for 30 minutes to form a 0.15 mol / L manganese nitrate solution.

[0082] By adjusting two different electrostatic coordination reaction solutions, the oxygen vacancy heterostructure is designed. The results show that the oxygen vacancy heterostructure obtained by using 0.015mol / L manganese chloride solution has good electrochemical energy storage characteristics. At a current density of 2mA / cm2, the area specific capacitance of the oxygen vacancy heterostructure obtained by using manganese chloride solution is 17700.32mF / cm2; the area specific capacitance of the oxygen vacancy heterostructure prepared by using manganese nitrate is 12580.32mF / cm2. Therefore, the present invention takes the oxygen vacancy heterostructure prepared by manganese chloride solution as the research object.

[0083] Figure 6 This is a SEM image after the electrochemical electrostatic coordination reaction. It can be seen that spinel structures ranging from several hundred nanometers appear on the surface of the nanosheets. The distribution of these spinel structures is relatively uniform. Some of them are self-stacked to form spinel clusters, and some are distributed on the surface of the nanosheets or between the nanosheets.

[0084] Figure 7 The HRTEM (and the inverse FFT line profile of the selected area) and SAED spectrum after the electrochemical electrostatic coordination reaction. The average lattice spacing measured is 0.248nm, corresponding to the (211) crystal plane of CoMn2O4. The SAED pattern characterizes the presence of the (211) crystal plane of CoMn2O4 and the (220) and (400) crystal planes of Mn3O4.

[0085] Figure 8This is the XRD spectrum after the electrochemical electrostatic coordination reaction. The diffraction peak at 2θ of 36.19° corresponds to the (211) crystal plane of CoMn2O4; the diffraction peaks at 2θ of 18.00° and 28.88° correspond to the (101) and (112) crystal planes of CoO; the diffraction peaks at 2θ of 30.81°, 58.40° and 76.01° correspond to the (220), (511) and (533) crystal planes of MnAl2O4. In summary, the phase composition after the electrochemical electrostatic coordination reaction is CoMn2O4 / Mn3O4 / MnAl2O4 (O V ).

[0086] Fig. 9 (a) CoMn2O4 / Mn3O4 / MnAl2O4(O V ) at current densities of 2, 4, 6, 8 and 10 mA / cm 2 The GCD curves at 1000.32, 14840.47, 12830.63, 10360.54 and 8983.31 mF / cm 2 , indicating its good energy storage characteristics and rate performance. Fig. 9 (b) CoMn2O4 / Mn3O4 / MnAl2O4(O V ) as the positive electrode, rGO as the negative electrode, KOH solution as the electrolyte, and the GCD curve of the assembled aqueous device. 2 When the area specific capacitance of the device is 229.38, 175.36, 163.28, 151.45 and 127.68 mF / cm 2 The device has an energy density of 81.56Wh / cm 2 The power density is as high as 639.93W / cm 3 ; At a power density of 3968.68W / cm 3 When the energy density is 45.40Wh / cm 2 .

[0087] Fig.10 This is the cycle stability test diagram of the device. At 8mA / cm 2 At a high current density of , the initial capacitance retention rate was 89.30% after 5000 cycles.

[0088] The present invention prepares a precursor alloy by vacuum arc melting and adopts a dynamic atomic dissolution self-assembly strategy to prepare a self-supporting integrated cobalt manganese oxide oxygen vacancy heterostructure independent electrode.

[0089] The present invention uses manganese salt as an electrochemical electrostatic coordination reaction solution, takes self-supporting integrated CoO / CoAl2O4 as a substrate, and adopts an electrochemical electrostatic coordination reaction strategy to construct a self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V )Oxygen vacancy heterogeneous site independent electrode.

[0090] The present invention provides a self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V )Oxygen vacancy heterogeneous site independent electrode. This oxygen vacancy heterogeneous site structure integrated independent electrode can be used as an anode in a supercapacitor.

[0091] The self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Oxygen vacancy heterogeneous sites are independent electrodes. The synergistic effect between oxygen vacancies and heterogeneous sites regulates the polarization electric field inside the material, provides a driving force for ion migration, and accelerates the charge response rate.

[0092] The self-supporting integrated CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) Oxygen vacancy heterogeneous site independent electrode material, no need for adhesives, conductive agents and current collectors, the integrated structural design has strong structural stability and long cycle life.

[0093] In addition, the present invention uses CoMn2O4 / Mn3O4 / MnAl2O4 (O V ) as the positive electrode, rGo as the negative electrode, and KOH as the electrolyte, and assembled into an aqueous device to explore its energy storage properties. The synergistic effect of oxygen vacancy defects and heterogeneous sites and the integrated structural design, CoMn2O4 / Mn3O4 / MnAl2O4(O V ) / / rGO asymmetric devices have good energy storage and service life. In addition, the preparation process of the present invention has easy-to-control structural morphology, the obtained product has stable performance, is suitable for industrial production, can be widely used in the field of energy storage and catalysis, and has far-reaching market prospects.

Claims

1. A method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode, It is characterized in that The following steps are involved: (1) Preparation of precursor alloy by vacuum arc melting furnace: Step 1: Weigh aluminum and cobalt metal particles according to an atomic ratio of 65:35, and melt them into alloy ingots in a vacuum arc melting furnace; Step 2: Cut the smelted alloy ingot into alloy sheets, remove oil and clean them, and then vacuum dry them for standby use; (2) Using dynamic atomic dissolution self-assembly strategy, design a self-supporting integrated cobalt aluminum oxide independent electrode: Step 3: First, place the alloy sheet cleaned and dried in step 2 in a 1-3 mol / L NaOH alkaline solution and keep it in a 50°C constant temperature water bath for 12-24 hours, then place it in a 2 mol / L HCl acidic solution and keep it in a 50°C constant temperature water bath for 12 hours to achieve the dissolution and self-assembly process of dynamic atoms; Step 4: After cleaning and drying the alloy sheet obtained in step 3, place it in a tube furnace and perform annealing treatment under an argon atmosphere to prepare a self-supporting integrated cobalt aluminum oxide independent electrode; (3) Preparation of self-supporting integrated CoMn by electrochemical electrostatic coordination reaction 2 O 4 / Mn 3 O 4 / MnAl 2 O 4 (O V ) Nanosheet spinel oxygen vacancy heterogeneous site independent electrode: Step 5: In an electrochemical workstation, the alloy sheet annealed in step 4 is subjected to an electrostatic coordination reaction to construct oxygen vacancy heterogeneous sites on the cobalt aluminum oxide independent electrode. The electrochemical electrostatic coordination reaction voltage is set to -1.0V to -1.5V, and the coordination reaction time is 10-30min. After the electrostatic coordination reaction, the sheet is taken out for cleaning and drying to prepare a self-supporting integrated CoMn 2 O 4 / Mn 3 O 4 / MnAl 2 O 4 (O V ) Nanosheet spinel oxygen vacancy heterosite as independent electrodes for supercapacitors.

2. The method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 1, It is characterized in that The pressure in the vacuum melting furnace in step 1 is 5×10 -3 MPa, the atmosphere during smelting was argon protective gas, and the alloy ingot was smelted 4 times.

3. The method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 1, It is characterized in that The size of the alloy sheet cut in step 2 is 10×10×1 mm.

4. The method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 1, It is characterized in that The steps of degreasing and cleaning the alloy sheet in step 2 are: ultrasonic cleaning in acetone, ethanol and deionized water for 5-15 minutes respectively.

5. The method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 1, It is characterized in that In step 2, the vacuum drying temperature is 50-70° C. and the time is 12-24 hours.

6. The method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 1, It is characterized in that In step 4, the temperature of the annealing treatment in the tubular furnace is increased at a rate of 5°C / min to 500-550°C, and maintained for 120-240 minutes.

7. The method for preparing a self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 1, It is characterized in that In step 5, the three-electrode system of the electrochemical electrostatic coordination reaction is composed of: a cobalt aluminum oxide independent electrode as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode. The electrochemical electrostatic coordination reaction solution is composed of: adding a manganese salt and urea in a molar ratio of 1:1 to water, and stirring to form a 0.15 mol / L reaction solution, wherein the manganese salt is manganese chloride or manganese nitrate.

8. A self-supporting integrated oxygen vacancy heterogeneous site independent electrode, It is characterized in that Prepared by the method according to any one of claims 1 to 7.

9. The self-supporting integrated oxygen vacancy heterogeneous site independent electrode according to claim 8 is used as a supercapacitor anode.